Pulled versus Pushed Monocanalicular Silicone Intubation in Adults with Lacrimal Drainage System Stenosis: A Comparative Case Series - Kasaee, Abolfazl; Eshraghi, Bahram; Ameli, Kambiz; Ghahvehchian, Hossein; Jamshidian-Tehrani, Mansooreh; Nabavi, Amin; Inanloo, Bahman (Journal of ophthalmology, 2021)
Purpose. To compare the success rate and complications of pulled versus pushed monocanalicular intubation in adults with incomplete lacrimal drainage system obstruction (lacrimal drainage system stenosis). Methods. Patients with lacrimal drainage system stenosis (Munk grade ≥3), including both nasolacrimal duct (NLD) stenosis and common canalicular stenosis, were recruited in this prospective comparative case series. Patients underwent probing and either Monoka (51 eyes) or Masterka (48 eyes) intubation under general or local anesthesia. Tubes were removed 4–14 weeks after the procedure. Six months after tube removal, Munk grades 0 and 1 were defined as a complete success, Munk grade 2 was defined as a partial success, and Munk grade ≥3 was defined as failure. All complications were recorded. Results. Ninety-nine eyes from 89 patients with lacrimal drainage system stenosis who underwent either Monoka (51 eyes) or Masterka (48 eyes) intubation were included. The mean (SD) age of the patients was 55.4 (12) years in the Monoka group and 53.5 (12.9) in the Masterka group. Groups were matched on demographics. Masterka intubation could not be performed in one eye. Complete and partial successes were observed in 52.9% (27/51) and 17.6% (9/51) of eyes in the Monoka group and 42.6% (20/47) and 12.8% (6/47) of eyes in the Masterka group, respectively (p=0.29). There was a trend toward a higher total success rate in patients with NLD stenosis treated with Monoka 66.7% (26/39) than Masterka 45.5% (15/33) intubation (p=0.07). This trend also existed in patients with common canalicular stenosis (83.3% (10/12) vs. 76.6% (11/14), p=0.75). Age, sex, bilateral involvement, and duration of intubation did not have a significant impact on the success rate. Early tube loss, slit puncta, and temporary superficial punctate keratopathy were observed complications. Conclusion. Intubation with the pulled monocanalicular silicone tube was associated with a slightly but not significantly higher success rate in adults with lacrimal drainage system stenosis. Patients with NLD stenosis may achieve better results with pulled silicone tubes.